Pengaruh Penggunaan Media Pembelajaran Tape Recorder Terhadap Hasil Belajar Siswa Kelas 5 Pada Mata Pelajaran Bahasa Indonesia - Nur Azizah; Wardah Putri Fa’izah; Hery Setiyawan (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research aims to describe the application of tape recorder learning media in Indonesian language learning in fifth grade elementary school learning. This journal research uses a quantitative approach with data collection methods. The results of this research indicate that the application of tape recorder learning media is an alternative in learning Indonesian. Apart from that, the application of learning media increases understanding of language concepts, improves students' skills, can improve learning activities, cognitive learning outcomes and students' language process skills, improves students' learning outcomes, improves learning outcomes and students' learning activities. Management of Indonesian language learning by implementing tape recorder learning media is very good. Student activities when learning Indonesian by applying the learning model are very good.